Molar-Incisor Hypomineralization (MIH). Prevalence among 16-year-old adolescents: A case-control study of children with a low Apgar score at birth and a study on tooth formation and antibiotics in mice - Schmalfuss, Andreas Jörn (UiT The Arctic University of Norway, 2022)
Background/Aims: Molar-Incisor Hypomineralization (MIH) is one of the most common dental developmental disorders with a global prevalence of 13%. The etiology of MIH is still elusive. The aims of this thesis were to report the prevalence of MIH in northern Norway, to investigate a possible association between birth asphyxia and MIH, and to document the effect of antibiotics on the developing enamel in neonatal mice were investigated. Methods: To assess the MIH prevalence, distribution, and severity of affected teeth, a cross-sectional health survey including 16-year-olds was performed. The diagnosis of MIH was based on clinical photographs. To examine the association between Apgar score ≤ 5 five min after birth and MIH, a cross-sectional case-control study of 8- to 10-year-old children was performed. The effects of gentamycin and ampicillin on the developing enamel were assessed in neonatal mice given intravenous injections. X-ray microtomography (micro-CT) was used for enamel analysis. Results: The prevalence of MIH in northern Norway was 13.9%. Affected canines were recorded in 22.8% of the participants with MIH. Only opacities were reported in 54% of the affected molars. There was no correlation between an Apgar score and the prevalence of MIH. The analysis showed significantly lower vol% in molars and incisors in addition to lower MD in the incisors in the study group. Conclusions: The prevalence of MIH (13.9%) as well as the distribution pattern and severity of affection were consistent with previous Scandinavian reports. Approximately one-quarter of all participants affected by MIH had at least one affected canine. An Apgar score ≤ 5 did not increase the incidence of MIH. Intervention with high-dose antibiotics given to neonatal mice influenced the development of molars and incisors. The analysis of teeth in neonatal mice with micro-CT could be a valid model for further research on MIH.